Bisphenol A induces apoptosis in response to DNA damage through c-Abl/YAPY357/ p73 pathway in P19 embryonal carcinoma stem cells. (30th March 2022) - Ren, Fei; Ning, Hongmei; Ge, Yaming; Yin, Zhihong; Chen, Lingli; Hu, Dongfang; Shen, Shanshan; Wang, Xinrui; Wang, Siting; Li, Rongbo; He, Junping
Abstract: Bisphenol A (2, 2-bis(4′-hydroxyphenyl) propane, BPA) is a well-known endocrine-disrupting compound that is widely used in various daily products and exhibits embryonic development toxicity and genotoxicity. However, the affected signaling pathways involved in embryonic development especially the interactions of involved proteins remain unclear. In our previous study (Ge et al., 2021), BPA induces DNA damage and apoptosis in Xenopus embryos, resulting in multiple malformations of larvae. However, the signaling pathways induced for apoptosis response to DNA damage are still not well elucidated. Here, we systematically elucidated the enriched pathways affected by BPA and illustrated the interactions of involved proteins. Results indicated that BPA affected multiple embryonic development pathways including Hippo, TGF-β, Wnt, and Notch pathways. Furthermore, the protein-protein interaction network suggested that the c-Abl/YAP Y357 /p73 pathway may play a key role in apoptosis induction in response to DNA damage. P19 embryonal carcinoma stem cells, as a developmental toxicity model, were treated with different BPA concentrations to establish an in vitro model to verify the role of the c-Abl/YAP Y357 /p73 pathway in apoptosis. BPA triggered DNA damage and significantly upregulated the expression levels of c-Abl, phosphorylated YAP Y357, phosphorylated p73 Y99, and cleaved caspase-3 protein ( p  < 0.05), thus decreasing cell viability and transcriptionally activating the p73 target genes Bax and Puma . These data suggested that BPA activated the c-Abl/YAP Y357 /p73 pathway in response to DNA damage. Imatinib, an inhibitor of tyrosine kinase c-Abl, significantly downregulated the elevated expression levels of p-YAP Y357, p-p73 Y99 and cleaved caspase-3 ( p  < 0.05) caused by BPA and then ameliorated the cell index of P19 cells in the BPA-treated group. Therefore, this substance restrained the phosphokinase activity of c-Abl and suppressed the c-Abl/YAP Y357 /p73 pathway. Results showed that the c-Abl/YAP Y357 /p73 pathway served as a mechanism for caspase-3 activation that induced the apoptosis response to DNA damage stress. Graphical Abstract: ga1 Highlights: BPA affects multiple signaling pathways involved in embryonic development. BPA induced DNA damage in P19 embryonal carcinoma stem cells. BPA induced apoptosis in response to DNA damage via the c-Abl/YAP Y357 /p73 pathway.